Assessing the combination of magnetic field stimulation, iron oxide nanoparticles, and aligned electrospun fibers for promoting neurite outgrowth from dorsal root ganglia in vitro. (1st September 2021) - Funnell, Jessica L.; Ziemba, Alexis M.; Nowak, James F.; Awada, Hussein; Prokopiou, Nicos; Samuel, Johnson; Guari, Yannick; Nottelet, Benjamin; Gilbert, Ryan J.
Abstract: Magnetic fiber composites combining superparamagnetic iron oxide nanoparticles (SPIONs) and electrospun fibers have shown promise in tissue engineering fields. Controlled grafting of SPIONs to the fibers post-electrospinning generates biocompatible magnetic composites without altering desired fiber morphology. Here, for the first time, we assess the potential of SPION-grafted scaffolds combined with magnetic fields to promote neurite outgrowth by providing contact guidance from the aligned fibers and mechanical stimulation from the SPIONs in the magnetic field. Neurite outgrowth from primary rat dorsal root ganglia (DRG) was assessed from explants cultured on aligned control and SPION-grafted electrospun fibers as well as on non-grafted fibers with SPIONs dispersed in the culture media. To determine the optimal magnetic field stimulation to promote neurite outgrowth, we generated a static, alternating, and linearly moving magnet and simulated the magnetic flux density at different areas of the scaffold over time. The alternating magnetic field increased neurite length by 40% on control fibers compared to a static magnetic field. Additionally, stimulation with an alternating magnetic field resulted in a 30% increase in neurite length and 62% increase in neurite area on SPION-grafted fibers compared to DRG cultured on PLLA fibers with untethered SPIONs added to the culture media. These findings demonstrate that SPION-grafted fiber composites in combination with magnetic fields are more beneficial for stimulating neurite outgrowth on electrospun fibers than dispersed SPIONs. Statement of significance: Aligned electrospun fibers improve axonal regeneration by acting as a passive guidance cue but do not actively interact with cells, while magnetic nanoparticles can be remotely manipulated to interact with neurons and elicit neurite outgrowth. Here, for the first time, we examine the combination of magnetic fields, magnetic nanoparticles, and aligned electrospun fibers to enhance neurite outgrowth. We show an alternating magnetic field alone increases neurite outgrowth on aligned electrospun fibers. However, combining the alternating field with magnetic nanoparticle-grafted fibers does not affect neurite outgrowth compared to control fibers but improves outgrowth compared to freely dispersed magnetic nanoparticles. This study provides the groundwork for utilizing magnetic electrospun fibers and magnetic fields as a method for promoting axonal growth. Graphical abstract: Image, graphical abstract